Low-Level Tritium Measurement in Tap Water in Bangkok Area and Annual Dose Estimation: 10.32526/ennrj/20/202200066 - Sudprasert, Wanwisa; Phattanasub, Archara; Srimork, Panuwat; Iamlae, Supaporn; Wongpaiboonsuk, Papavee; Wongwechwinit, Ploypailin (Environment and Natural Resources Journal, 2022)
Monitoring of tritium concentration in tap water is an essential tool to determine the effective dose received from tap water. Liquid scintillation counting (LSC) is a widely used technique for determining tritium in water. Due to the very low activity of tritium in tap water, its detection requires a high-efficiency LSC with the lowest minimum detectable activity (MDA). Low-level tritium analysis in tap water were performed in two LSC models using conventional distillation techniques. The optimal conditions with the lowest MDAs were applied to determine the tritium concentration in the tap water distributed from two main sources located in the Bangkok metropolitan region: Bang Khen and Maha Sawat water treatment plants (WTPs). Twenty-six tap water samples were collected from petrol stations located around both water treatment plants. The results revealed that the amount of tritium in the tap water around the Bangkhen WTP was between 1.88-2.63 Bq/L with an average of 2.28±0.28 Bq/L, whereas those from the Maha Sawat WTP were between 2.01-2.69 Bq/L with an average of 2.44±0.26 Bq/L, which are far below the World Health Organization’s (WHO) guideline limit (10,000 Bq/L) for drinking water. The annual effective dose (AED) for infants, children and adults obtained from tap water samples around the Bangkhen WTP were 0.010, 0.014, and 0.030 µSv/year, respectively, and those from the Maha Sawat WTP were 0.011, 0.015, and 0.032 µSv/year, respectively, which are far below the WHO’s guideline limit (100 µSv/year).